Long-Haul mmWave Sky Links: A Multi-Hop NFP-Based Design and Analysis - Abdullateef Almohamad (16870074) (2023)
Networked flying platforms (NFPs) have emerged as a favorable solution to extend the network coverage and/or capacity in temporary scenarios, such as disasters or mega-size events, thanks to their flexibility and cost efficiency. However, in order to provide a reliable multihop link through NFPs, multiple parameters should be considered and optimized, such as the antenna gains, and the number of NFPs required to achieve a certain level of quality of service (QoS). Furthermore, the design of such parameters when considering the hovering fluctuation of NFPs becomes more challenging. In this paper, we study the performance of a long millimeter wave (mmWave) link through multiple NFPs to connect a remote area with the core network taking into account the fluctuation of NFPs. In specific, we derive the outage probability (OP) for such a system under practical considerations, such as NFP fluctuation variance, realistic 3D radiation patterns, gaseous absorption losses, number and distribution of NFPs. Furthermore, we propose a spatial formation for NFPs to reduce interference along the path. Extensive simulations are provided to validate the analytical findings and to reveal insightful trade-offs that help in designing such links. Other Information Published in: IEEE Open Journal of Vehicular Technology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/ojvt.2023.3241293